Introductory Thoughts – The Role of Communication in the World Related to the Children - Váradi-Csema, Erika (Interdisciplinary and Child-Friendly Communication, 2025)
The purpose of this short introductory chapter is to highlight, through a few examples, the key importance of communication in the social integration and socialisation process of young people, and their subsequent turning into perpetrators or victims – before moving on to topics that are discussed in greater depth in succeeding chapters of the book. The individual factors in this complex system of relationships influence each other both directly and indirectly. At the same time, the level of children’s communication skills – or their impairment or lack thereof – in itself influences the extent to which and the success with which they will be able to exercise their guaranteed children’s rights.Keywords: communication, developmental language disorder, DLD, criminological aspects, child andyouth crime